2021
DOI: 10.1002/term.3225
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization strategies in tissue engineering approaches for soft tissue repair

Abstract: Insufficient vascularization during tissue repair is often associated with poor clinical outcomes. This is a concern especially when patients have critical-sized injuries, where the size of the defect restricts vascularity, or even in small defects that have to be treated under special conditions, such as after radiation therapy (relevant to tumor resection) that hinders vascularity. In fact, poor vascularization is one of the major obstacles for clinical application of tissue engineering methods in soft tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 95 publications
0
55
0
Order By: Relevance
“…Therefore, having a uniform and continuous cell layer on the luminal surface of the graft seems to be a prerequisite for obtaining a hemocompatible small-diameter TEVG ( Pashneh-Tala et al, 2016 ). Adding a luminal coating step prior to cellularization in the TEVG manufacture protocol is strongly recommended because it can create a microenvironment that can modify cell behavior by enhancing cell adhesion, proliferation and/or differentiation ( Masson-Meyers and Tayebi, 2021 ). We are one of the multiple teams concerned by the lack of small-caliber vascular substitutes and seeking to develop a long-term patent and efficient small-diameter TEVG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, having a uniform and continuous cell layer on the luminal surface of the graft seems to be a prerequisite for obtaining a hemocompatible small-diameter TEVG ( Pashneh-Tala et al, 2016 ). Adding a luminal coating step prior to cellularization in the TEVG manufacture protocol is strongly recommended because it can create a microenvironment that can modify cell behavior by enhancing cell adhesion, proliferation and/or differentiation ( Masson-Meyers and Tayebi, 2021 ). We are one of the multiple teams concerned by the lack of small-caliber vascular substitutes and seeking to develop a long-term patent and efficient small-diameter TEVG.…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenesis assays performed in this study showed the capacity of the CS‐S system to significantly increase and accelerate the capacity of vascular‐like structure formation in all analyzed parameters at 6 h, probably due to the controlled release of important growth, resulting in sustained angiogenesis. This form of analysis of the angiogenesis process is widely validated in the literature, with Matrigel® being the most used base, due to having the ability to evaluate potential pro‐angiogenic factors (Masson‐Meyers & Tayebi, 2021; Stryker et al., 2019). Recruited cells need nutrition to differentiate and form new tissue, and the root canal structure is surrounded by hard tissue with only a foramen that allows the entry of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue injuries, including skin, muscle, tendon, and nerve injury, affect millions of people every year [ 1 , 2 , 3 , 4 , 5 , 6 ]. Studies on tissue repair and regeneration have focused primarily on skin wound healing; however, for complete repair of composite soft tissue defects, healing of tendons, skeletal muscles, and peripheral nerves will also be required to restore function.…”
Section: Introductionmentioning
confidence: 99%